PEMBERDAYAAN KEAGAMAAN ISLAM BERBASIS MASJID DI PAGUTAN BARAT MATARAM - Muhamad Dimyati; Muslehuddin Muslehuddin; Haerul Akmal (STAI Darul Qalam Tangerang, 2026)
Mosque-based religious empowerment is necessary because mosques at the community level are often not managed as centers of education, guidance, social solidarity, and youth regeneration. This article aims to analyze the effectiveness of mosque-based Islamic community empowerment in RW 304, Pagutan Barat Village, Mataram District, Mataram City. The community service method applied a community development approach through observation, problem identification, program formulation, intervention, and evaluation. Data were obtained from program documentation, participation records, and pre-post evaluation instruments involving 60 respondents. The analysis used descriptive quantitative techniques through mean scores, score differences, and percentage increases. The results show that the empowerment score increased from 3.05 to 4.18 on a 1-5 scale, equal to a 37.0% increase. The highest increase occurred in concern for worship facilities and Qur'an learning media, reaching 55.4%. Youth participation increased by 42.6%, although its final score remained lower than other indicators. The findings confirm that mosques can function effectively as empowerment centers when Islamic education, social da'wah, welfare, and youth regeneration are integrated. The article contributes a four-pillar mosque empowerment model that can be replicated in urban village communities.